Incidence, management and outcome of women requiring massive transfusion after childbirth in the Netherlands: secondary analysis of a nationwide cohort study between 2004 and 2006 - Paul I. Ramler; Thomas van den Akker; Dacia D. C. A. Henriquez; Joost J. Zwart; Jos van Roosmalen (BMC, 2017)
Abstract Background Postpartum hemorrhage remains the leading cause of maternal morbidity and mortality worldwide. Few population-based studies have examined the epidemiology of massive transfusion for postpartum hemorrhage. The aim of this study was to determine the incidence, management, and outcomes of women with postpartum hemorrhage who required massive transfusion in the Netherlands between 2004 and 2006. Methods Data for all women from a gestational age of 20 weeks onwards who had postpartum hemorrhage requiring eight or more red blood cell concentrates were obtained from a nationwide population-based cohort study including all 98 hospitals with a maternity unit in the Netherlands. Results Three hundred twenty-seven women who had postpartum hemorrhage requiring massive transfusion were identified (massive transfusion rate 91 per 100,000 deliveries (95% confidence interval: 81-101)). The median blood loss was 4500 mL (interquartile range 3250-6000 mL) and the median number of red blood cell concentrates transfused was 11 units (interquartile range 9-16 units). Among women receiving massive transfusion, the most common cause of hemorrhage was uterine atony. Eighty-three women (25%) underwent hysterectomy, 227 (69%) were admitted to an intensive care unit, and three women died (case fatality rate 0,9%). Conclusion The number of women in the Netherlands who had postpartum hemorrhage treated with massive transfusion was relatively high compared to other comparable settings. Evidence-based uniform management guidelines are necessary.